2008
DOI: 10.4025/cienccuidsaude.v7i0.6558
|View full text |Cite
|
Sign up to set email alerts
|

A resposta do peso e da composição corporal à inclusão da dieta de cafeteria e treinamento físico aeróbio em diferentes fases do desenvolvimento

Abstract: RESUMOO objetivo deste estudo foi identificar as alterações no peso e na composição corporal relacionadas à inclusão da dieta de cafeteria e treinamento físico aeróbio em diferentes fases do desenvolvimento. Foram utilizados ratos da linhagem wistar divididos em dois procedimentos experimentais, sendo um iniciado com dieta de cafeteria e treinamento físico com animais aos 21 dias de vida (sedentários cafeteria, SCa21; treinado cafeteria, TCa21; sedentário controle, SC21 e treinado controle TC21) e outro com di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Experimental model of obesity: The model used to induce obesity was the Cafeteria diet (CAF) [8]. Thus, the animals were provided with normal diet ad libitum and a daily selection of grocery foods selected from a list of twelve items (Table 1), adapted from Almeida, et al [9]. The diet was maintained for 20 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental model of obesity: The model used to induce obesity was the Cafeteria diet (CAF) [8]. Thus, the animals were provided with normal diet ad libitum and a daily selection of grocery foods selected from a list of twelve items (Table 1), adapted from Almeida, et al [9]. The diet was maintained for 20 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…A study by Almeida et al (2008) showed that an increase in the hepatic lipid content occurs proportionally to the original value. The effects of exercise training in this study are possibly associated with the effects of nutritional intake, i.e., the diet of the EO animals may have mitigated the effects of physical training.…”
Section: Discussionmentioning
confidence: 99%
“…9 Thus, the animals were provided with normal diet ad libitum and a daily selection of grocery foods selected from a list of 16 items (►Table 1), adapted from Almeida et al, 2008. 10 The feed was changed daily for the animals not to get used to the same food and consequently reject it. There was good acceptance of the CAF diet by the animals, mainly sausage, hamburger, bologna, and wafer.…”
Section: Experimental Model Of Obesitymentioning
confidence: 99%